Parental Support on College Students’ Career Adaptability: The Role of Proactive Personality as Mediator - Hartanto, Natassha Safira Abigail; Salim, Rose Mini Agoes (Jurnal Ilmu Pendidikan, 2021)
In dealing with the changes posed by the industrial era 4.0, college students need to have career adaptability. One of the factors that influence the development of career adaptability is parental support. However, some previous studies have shown inconsistencies in the influence of parental support on career adaptability. The inconsistency of the results indicates that there is the involvement of internal factors, namely proactive personality. This study aims to examine the role of proactive personality in mediating the effect of parental support on a student’s career adaptability. Participants involved in this research were undergraduate students (N equals 551) from various universities in Jakarta, Bogor, Depok, Tangerang, and Bekasi, who are in their 6th semester or more. The three research variables were measured using The Career Adapt-Ability Scale (CAAS), The Career-Related Parent Support (CRPSS), and the Proactive Personality Scale (PPS). Data processing was performed statistically using Pearson Correlation and PROCESS macros from Hayes. The results showed that parental support can influence career adaptability through proactive personality. Based on the limitations of this study, further research is suggested to consider the role of personality in parents, the characteristics of participants, and other factors that are likely to affect career adaptability.